A supply curve analysis for the Icelandic Housing Financing Fund bond market - Hannes Árdal 1981- (2013)
Risk management deals with three types of financial risks: market risk, credit risk and liquidity risk. Much has been written about both market and credit risk but substantially less has been written about liquidity risk. Liquidity risk has been modelled for securities as a supply curve where the price obtained in a trade of a given security is reflected not only in the time of the trade but also in the size and direction (buy or sell orders). In this thesis, data provided by the Icelandic Stock Exchange is used to examine the supply curve, and thus the liquidity, of three bonds traded in Iceland. Four different models for the supply curve will be presented and fitted to actual data. The supply curve is shown to exist and therefore it is shown that size and direction of a trade does affect the price obtained in a trade. In conclusion, the model most likely to be the best to describe the liquidity for the given bonds is selected. The model that best fitted the provided data was the S-shaped logarithmic model where the rather high bid-ask spread and market participants’ tendency to place their orders alongside other orders were well captured. Áhættustýring á fjármálamarkaði fæst aðallega við þrjár mismunandi áhættur; markaðsáhættu, endurgreiðsluáhættur og seljanleikaáhættu. Töluvert hefur verið ritað um fyrri tvær áhætturnar en mun minna um seljanleikaáhættu. Seljanleikaáhættu á verðbréfi hefur verið lýst með framboðskúrfu (e. Supply Curve) en í því felst að verð í viðskiptum með viðkomandi verðbréf er ekki einungis háð tímasetningu viðskiptanna heldur einnig magni í viðskiptunum og því hvort um kaup eða sölu á verðbréfinu sé að ræða, þ.e. átt viðskiptanna. Í þessari ritgerð eru notuð gögn frá Kauphöll Íslands til að rannsaka framboðskúrfu, og þar með seljanleika, þriggja skuldabréfa í Kauphöll Íslands. Fjögur mismunandi líkön fyrir framboðskúrfuna eru sett fram og aðhvarfsgreiningu er beitt til að aðlaga líkönin að raunverulegum gögnum. Sýnt er fram á að framboðskúrfan sé raunverulega til og þar með að magn og ...